Pengaruh Kualitas Pelayanan, Kualitas Produk dan Evaluasi Harga Terhadap Kepuasan Pelanggan Quick Chicken Jl. Dharmahusada, Surabaya - SUYOTO, Tony (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This research backgrounded by the competition in fast food restaurant especially local frenchise. This phenomena supports every company to improve both its standard of service and product to meet the consumersâ€™ need. And the objective of this research is to analyze the influence of service quality, product quality and the price evaluation towards the consumersâ€™ satisfaction. Then library research is conducted and also hypothesis arrangement as well as the data obtained from the spreading questionaires to the 150 customers Quick Chicken Jl. Dhrmahusada, Surabaya by using Purposive Sampling technique and after that data analyzing is conducted, the data is obtained by using quantitative data analyzing. This quantitative analyzing covers : Validity, Reliability, Classic Assumption, Double Regretion Analyzes, Hypothesis Test through â€œtâ€ and â€œFâ€ tests, as well as Determination Coeffisient Analyzes ( R2). The hypothesis test using â€œtâ€ test shows that Service Quality and Product Quality analyze were significantly proved to influence the dependent variable of Customersâ€™ Satisfaction.